Estudo analítico da associação de lisinopril e hidroclorotiazida cápsulas magistrais por cromatografia líquida de alta eficiência - Araújo, Lindsay Paiva De (2010)
Combinations of drugs have been effective in controlling hypertension pressure. Drugs such as hydrochlorothiazide and lisinopril, in low dosages, for moderate to severe hypertension, without effects pronounced side, has been recommended. Due to lack of monograph for specific analysis of drug combination, the objective work is to develop analytical methodology to assess the dissolution profile of tablets containing these assets and their quantify, given the different processes and ingredients used in manipulation. For the quantification of the assets in the pharmaceutical form capsule, liquid chromatography was used to high efficiency and the in vitro release study, we used 0.1 mol L−1 HCl (volume 900 mL) as dissolution medium, basket apparatus, speed of 100 rpm and time collection of 60 minutes. The analytical method validation and testing of dissolution followed the RE Nº 899 of ANVISA. The analytical method demonstrated linearity at concentrations from 11 to 21 μg mL−1 and 18 to 33 μg mL−1, with r > 0.99 for hydrochlorothiazide and lisinopril, respectively. There was no interference from excipients in the study of selectivity.The accuracy of method had a value of RSD < 2 %, indicating satisfactory precision. For the accuracy of the method, the recovery values for samples A, B and C, respectively, from 98 to 102 %. The method was robust to varying the oven temperature (50 ± 5 ° C) and the flow of mobile phase (0.4, 0.5 and 0.6 mL/min). Validation of the in vitro showed linearity in the concentration ranges from 3 to 17 μg mL−1 and 4 to 26 μg mL−1, r > 0.99 for hydrochlorothiazide and lisinopril, respectively. The assay was selective, with no interference from excipients and wrappers. The assay precision showed RSD value of less than 5 % indicating satisfactory precision. The average values of accuracy for samples A, B and C ranged from 95 to 105 %. All the capsules analyzed (A, B and C) were adopted in testing of quality. This study provided support for the preparation of a pharmacopoeial monograph order to control quality of the drugs in capsules manipulated in pharmacies, as there is no official method described.